Phylogeography and hybridization of corvid birds in the Palearctic Region - A. P. Kryukov (Вавиловский журнал генетики и селекции)
Natural hybridization increases a lot phenotypic and genetic diversity and shapes intra-species patterns, which is a subject of phylogeography. We studied mitochondrial and complete genome variation in the bird family Corvidae, genera Corvus, Pica, Cyanopica, Perisoreus and Nucifraga. In the classic case of natural hybridization between carrion and hooded crows in Siberia, we found no decreased fitness of hybrids, but instead positive assortative mating which should restrict hybrid zone width. Several genetic markers were unable to discriminate between pure carrion and hooded crows. Mitochondrial DNA sequences revealed no difference between carrion and hooded crows, but instead two diverged haplogroups within the eastern part of the distribution range of the carrion crow. NGS resulted in a clear pattern of diversification of pure forms and hybrids (by using SNPs), and showed genomic regions of increased variability, the so-called “speciation islands”. Comparing European and Siberian crow hybrid zones, differences in genome regions bearing genes of melanogenesis supposedly under divergent selection were found. Comparative phylogeographic analysis of 10 widely distributed Palearctic species revealed two kinds of patterns: one with a division into two haplogroups, western and eastern, and another one without such a division. These two phylogeographic patterns might be explained by different habitat preferences: mainly open fields for the first group and forests for the second one. One glacial refuge was assigned to the latter group, while west-east group species might have survived in several refuges. One of such species, the Eurasian magpie (Pica pica) has a gap in its range in Transbaikalia, which is currently shrinking before our eyes. The two subspecies divided by this gap differ in phenotype, mtDNA and vocalization. In their young contact zone, some hybridization occurs with small introgression limited by certain post-zygotic isolation.